It is Necessary to Increase the Training and Motivation of Primary Care Health Professionals in the Face Of Rare Diseases in Spain - Pérez, Susana Portela; Cameselle-Cortizo, Lucía; Cruz, Teresa Calheiros; Rodríguez-Fernández, Vanesa; Cameselle-Teijeiro, Jorge F (British Journal of Healthcare and Medical Research, 2024)
Background: Rare diseases (RDs) are defined as low prevalence diseases with great heterogeneity. Globally, they constitute an important public health problem. Most of them are incurable, chronic and have a great family impact. The objective of this study was to investigate the knowledge about RDs among primary care health professionals (137 doctors and 113 nurses) in our health area (Vigo, Spain). Methods: A total of 250 primary care health professionals, randomly chosen, completed an anonymous survey to evaluate their level of knowledge about aspects related to RDs. The survey contained a questionnaire (seven questions) related to basic aspects of rare diseases. Results: Primary care health professionals showed very poor knowledge about the impact of RDs on public health. There were no statistically significant differences when comparing the responses of doctors versus nurses in any of the responses obtained (p > 0.05). Conclusions: Among the main challenges facing RDs is shortening the diagnostic delay and providing comprehensive care. Primary care health professionals should play a key role, since they are the gateway to the health system. Unfortunately, the results of our survey reveal very poor knowledge about basic aspects of RDs. It is necessary to increase training and motivation if we want to improve the health care provided from primary care to patients with RDs.